Charles procedure combined with staged subcutaneous excision in treating a case of chronic massive lymphedema: a case report - Verma, Nimesh; Maisuria, Rushabh; Patel, Amit; S., Sankhya Bhat (International Surgery Journal, 2020)
Lymphedema in its advanced stage is a physically and psychologically debilitating condition as conservative management alone in this condition, barely makes any difference in patient’s quality of life. Here we present a case report where we were able to successfully treat our patient of massive lymphedema and help him walk on his feet, by an approach where we combined Charles procedure and staged subcutaneous excision of soft tissue.